Cholinergic Partition Cells and Lamina X Neurons Induce a Muscarinic-Dependent Short-Term Potentiation of Commissural Glutamatergic Inputs in Lumbar Motoneurons - Bertrand, Sandrine S.; Cazalets, Jean-René (Frontiers in Neural Circuits, 2011)
Acetylcholine and the activation of muscarinic receptors influence the activity of neural networks generating locomotor behaviour in the mammalian spinal cord. Using electrical stimulations of the ventral commissure, we show that commissural muscarinic (CM) depolarisations could be induced in lumbar motoneurons. We provide a detailed electrophysiological characterisation of the muscarinic receptors and the membrane conductance involved in these responses. Activation of the CM terminals, originating from lamina X neurons and partition cells, induced a pathway–specific short-term potentiation (STP) of commissural glutamatergic inputs in motoneurons. This STP is occluded in the presence of the muscarinic antagonist atropine. During fictive locomotion, the activation of the commissural pathways transiently enhanced the motor output in a muscarinic-dependent manner. This study describes for the first time a novel regulatory mechanism of synaptic strength in spinal locomotor networks that can potentially account for motor task-related modulatory influences in these circuits.